Comparison of Car Loan Interest in Malaysia Using a Web-Based Calculator - MUHAMMAD NASHARUL SYAFEEQ BIN MOHD HANAFI,; Pn Cik Sri Mazzura Binti Muhammad Basri, (Enhanced Knowledge in Sciences and Technology, 2023)
This research highlights the aspect to help Malaysians to compare which bank is the best to make loan and help to avoid people from the risk of default. The objective of the study is operating a car loan calculator to compare car loan interest and analyse car loan interest on different rate. Conducting this research to make a web-based calculator and calculate interest. The use of XAMPP Control Panel and Microsoft Excel to handle the web-development tools and the calculating method. We use the function of the localhost as the hostname that refer to the local machine of the car loan calculator. We build a payment schedule to keep track all the important information related to the loan. We created a car loan web-based calculator to help people compare the interest. The aim is to make people more understand the use of car loan and to make comparison of the car loan interest given in the Malaysia. The result of the car loan calculator was in two aspect as the structure and the main function of the calculator and analysis of the different rate of interest. We have been successfully constructing the car loan calculator by using Microsoft Excel and XAMPP Control Panel. We have been successfully achieved two objectives of this research to operate a car loan calculator to compare the car loan interest and analyse car loan interest at different rates. Recommendation is to make this calculator to be online and build the currency converter from the US Dollar to the Ringgit Malaysia, and monthly payment can be generated from it.